Catholiques français et chrétiens palestiniens :pour une sociologie relationnelle de la solidarité - Caterina Bandini (Les Cahiers d’EMAM, 2020)
From a relational approach, this article sheds new light on the solidarity between a segment of French catholicism and the Palestinian Christian communities. For this purpose, the article engages with the discourse and practices of French Catholics concerning the Israeli-Arab conflict, as well as with social and political transformations within the Palestinian Christian population. The solidarity networks differ significantly from most French Catholic mobilizations in favor of “Eastern Christians,” which are related to right-wing identity politics. The call for solidarity comes from a sector of Palestinian Churches that is involved, since the late 1980s, in a Liberation Theology movement, and in the creation of alternative pilgrimage tours. These tours, called “living stone pilgrimages,” lead both groups of actors to question their religious and national identity, and the meaning of their commitment as Christians for justice and peace in Palestine.